Detailed characterization of complex banding in air-cooled bainitic steels - MORALES-RIVAS, LUCIA; Roelofs, Hans; Hasler, Stephan; Garcia-Mateo, Carlos; Caballero, Francisca G. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
The presence of banding in a hot-rolled air-cooled bainitic steel has been thoroughly characterized. The banded microstructure was observed due to distinctive sensitivities to the etching agent. Microstructural and crystallographic studies by means of Scanning Electron Microscopy and Electron Backscatter Diffraction did not reveal any substantial differences between bands and matrix. However, solute segregation of some alloying elements was detected by Wavelength-Dispersive Spectroscopy, being found that bands are enriched in Cr, Mo and Si and depleted in Mn. Finally, a set of theoretical calculations suggested that the solidification mode is responsible for such unusual partitioning behavior, which is beneficial in terms of the bainitic transformation.